Early applicability of retinopathy of prematurity score (ROPScore) and serum insulin growth factor-1 (IGF-1) for predicting treatment-requiring retinopathy of prematurity: a prospective cohort study - Aliaa Adel Ali; Nancy Abd El-Salam Ahmed Gomaa; Basma Samir Kamil; Ahmed Awadein; Heba Baz; Esraa Ahmed Elmazzahy (Egyptian Pediatric Association Gazette)
Abstract Background Retinopathy of prematurity is a leading cause of blindness especially in developing countries where the accessibility to screening may not be available. Therefore, early prediction could help reallocate the resources for those at high risk. Objectives This study aimed to evaluate the accuracy of the retinopathy of prematurity score (ROPScore) and serum insulin-like growth factor-1 (IGF-1) for predicting treatment-requiring retinopathy of prematurity. Methods This prospective cohort study included 87 preterm neonates (≤ 32 weeks). Neonates were screened using digital fundus photography with indirect ophthalmoscopy performed when retinopathy of prematurity changes was detected. Serum insulin-like growth factor-1 was measured in the 3rd week of life. Results Nine cases (10.3%) developed treatment-requiring retinopathy of prematurity, while 78 patients had mild retinopathy of prematurity. According to logistic regression analysis, lower birth weight and longer duration of assisted ventilation were independent risk factors for treatment-requiring retinopathy of prematurity. At the 2nd week of life, cut-off value of 14.95 for the retinopathy of prematurity score showed a sensitivity of 100% and a specificity of 67.9% for predicting treatment-requiring retinopathy of prematurity. Moreover, serum insulin-like growth factor-1 was significantly lower in patients with treatment-requiring retinopathy of prematurity (p < 0.001). Conclusions ROPScore applied at week 2 and week 6 of life showed the same sensitivity and specificity to predict treatment-requiring retinopathy of prematurity. Furthermore, serum insulin-like growth factor-1 in the 3rd week of life was significantly lower in patients with treatment-requiring retinopathy of prematurity.